2012
DOI: 10.5539/jfr.v1n3p219
|View full text |Cite
|
Sign up to set email alerts
|

A Box-behnken Design for Characterizing Chinese Truffles (Tuber indicum) Aroma by HS-SPME-GC-MS

Abstract: The aim of the present investigation is to fully characterize the aroma of Chinese truffles (Tuber indicum) by headspace solid phase microextraction (HS-SPME). To develop an objective method to extract aroma compounds, four different fibers were studied and a Box-Behnken design (BBD) was applied. From the statistical analysis of the experimental result, it was able to determine that the most important factor was the extraction temperature and the optimum extraction conditions were as follows: extraction time 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Bis(methylthio)methane has always been considered as the most important sulfide in Italian white truffle ( Tuber magnatum Pico ) research [26] and it has also been found to play an important role in T2 samples. In addition to sulfur compounds, 2-methyl-butanal and 3-methyl-butanal were studied as important aroma compounds in different truffles [27,28], however, T3 samples had much less rough sulfide odor and more focused on 2-methyl-butanal and 3-methyl-butanal, which provided strong nutty and grain aroma. The AI of phenylacetaldehyde was also very high in T3 sample.…”
Section: Resultsmentioning
confidence: 99%
“…Bis(methylthio)methane has always been considered as the most important sulfide in Italian white truffle ( Tuber magnatum Pico ) research [26] and it has also been found to play an important role in T2 samples. In addition to sulfur compounds, 2-methyl-butanal and 3-methyl-butanal were studied as important aroma compounds in different truffles [27,28], however, T3 samples had much less rough sulfide odor and more focused on 2-methyl-butanal and 3-methyl-butanal, which provided strong nutty and grain aroma. The AI of phenylacetaldehyde was also very high in T3 sample.…”
Section: Resultsmentioning
confidence: 99%